2016
DOI: 10.1523/jneurosci.1090-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Inhibitory Feedback from Horizontal Cells to Photoreceptors: Implications for an Ephaptic Mechanism

Abstract: Inhibitory feedback from horizontal cells (HCs) to cones generates center-surround receptive fields and color opponency in the retina. Mechanisms of HC feedback remain unsettled, but one hypothesis proposes that an ephaptic mechanism may alter the extracellular electrical field surrounding photoreceptor synaptic terminals, thereby altering Ca 2ϩ channel activity and photoreceptor output. An ephaptic voltage change produced by current flowing through open channels in the HC membrane should occur with no delay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…Warren et al . () also recorded individual cones, but in contrast to Vroman et al . (), they manipulated the membrane potential of the presynaptic HC directly.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Warren et al . () also recorded individual cones, but in contrast to Vroman et al . (), they manipulated the membrane potential of the presynaptic HC directly.…”
Section: Introductionmentioning
confidence: 71%
“…This, however, is in contrast to a study in which feedback signals in cones displayed a latency of ∼10 ms (Warren et al . ). This discrepancy may have resulted from the different ways HC feedback was evoked in the two studies: Vroman et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…When the initial image falls on the retina, it undergoes amplification 100,000 times through chemical and electrical transduction during lateral inhibition [33]. Direct electric conduction from one neuron to another (especially those connected laterally) begins at photoreceptor synapses without the need for a neurotransmitter [37]. It has also been suggested that proton concentration carries feedback signal to cones, and is regulated by horizontal cells [38].…”
Section: Visual Processing and Lateral Inhibitionmentioning
confidence: 99%
“…Inhibitory signals in the OPL and IPL are essential in mediating computational elements of retinal functions, such as forming the classical antagonistic center and surround regions of the receptive fields of GCs (Cook & McReynolds, ; Flores‐Herr, Protti, & Wassle ; Vigh & Witkovsky, ; Werblin, ) or coding for the direction of visual stimulus movement (Caldwell Caldwell, Daw, & Wyatt ). Whereas in the OPL feedback inhibition from HCs to rod (Babai & Thoreson, ) and cone photoreceptors (Hirasawa & Kaneko, ; Verweij, Kamermans, & Spekreijse, ; Warren, Van Hook, Tranchina, & Thoreson, ) might influence BC signaling indirectly, direct GABAergic feed forward HC inputs to mammalian ON BCs (Duebel et al, ) were also documented. The axon terminals of BCs in the IPL receive extensive GABAergic and/or glycinergic feedback inhibition from ACs (Eggers & Lukasiewicz, ; Grimes, ).…”
Section: Introductionmentioning
confidence: 99%